Can we build resilience by way of creativity? Artistic ventures in a London hospice. (28th February 2020) - Hirschmann, Thomas; Hartley, Nigel; Roth, Steffen
Resilience and stress management are considered key factors for entrepreneurial success. In this research we propose that controlled, creative confrontation with adversity can help overcome stressful experience by fostering resilience. Our research is based on a neuronal network model that considers resilience in its relation to creativity. This model is applied to several cases at the UK hospice that successfully use art to deal with the stressful conditions of dying inpatients. On this background we outline the concept of 'Controlled Creative Confrontation' that harnesses the creativity-inherent potential for catalytic change to build resilience and permanently transform patient self-perception. This concept is illustrated in three exemplary cases of patients who successfully navigated their impending death by using art to confront, overcome and rebuild coping strategies in the face of ultimate adversity. Describing these cases, we acknowledge the specific aspects of resilience believed to be fostered by creativity. We conclude the research giving an outlook on suggested future studies providing quantitative support for and deeper insight into, the causal relationship between creativity and resilience and their impact on the success of entrepreneurial ventures.